How to facilitate peer support – learnings from the development of a peer support program for people with T2DM via instant messaging service to improve diabetes self-management - Ursula Hemetek; Tatjana Aubram; Johanna Grüblbauer; Elisabeth Höld (Frontiers in Clinical Diabetes and Healthcare)
This study explores the use of Instant Messaging Services (IMS) for peer support among individuals with Type 2 Diabetes Mellitus (T2DM). Leveraging the popularity of IMS within the affected age group, the DiabPeerS study implemented a peer support intervention aimed at improving long-term blood glucose levels (HbA1c) in a randomized controlled trial (RCT). This article describes the development and acceptance of the IMS intervention used in the DiabPeerS study. The intervention included a communication strategy and content designed for lay moderators to facilitate group interaction among people with Type 2 Diabetes mellitus (PWT2D). The intervention’s acceptance was determined by conducting participant interviews, moderator meetings, and analysis of IMS chat protocols. Results indicate that the intervention was well-received, with participants engaging in meaningful exchange about diabetes self-management (DSM). However, those less familiar with online communication may benefit from preparational training and initial face-to-face meetings could enhance group cohesion. This research offers insights into the practical application of IMS for diabetes peer support, highlighting both its benefits and room for improvement.